Sodium-glucose co-transporter 2 inhibitors – a review article - Makuch, Marcin; Makuch, Marcelina; Krzewicka-Romaniuk, Ewa; Dzida, Grzegorz (Journal of Education, Health and Sport, 2019)
Antihyperglycemic interventions have centered on increasing insulin availability, improving insulin sensitivity or restoring β-cell activity to normalize plasma glucose levels in patients with type 2 diabetes mellitus. An alternative strategy is to enhance urinary glucose excretion by targeting renal sodium-glucose co-transporters (SGLTs). Sodium-glucose co-transporter 2 (SGLT2) inhibitors reduce blood glucose by increasing urinary glucose excretion and present a valuable therapeutic option for the treatment of type 2 diabetes. Presently, clinically available SGLT2 inhibitors include canagliflozin, dapagliflozin and empagliflozin.